(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
Genesis (Manuscrits - Recherche - Invention) is a biannual French periodical promoted by the Institut des textes et manuscrits modernes (ITEM) of Paris, the center of researches on genetic criticism, which has many team working on the main authors of French and European Literature of the XVIIth Century (Rousseau, Voltaire), of the XIXth century (Flaubert, Zola), of XXth century (Proust, Joyce, and also Aragon, Barthes, Celan, Valéry), of Philosophy (Nietzsche, Sartre). Genesis was founded in 1992 and is now edited by PUPS. Presses de l’Université Paris-Sorbonne, under the direction of Daniel Ferrer and Almuth Grésillon. Two years after the prints, issues are available on the periodical’s website: http://genesis.revues.org/ This is the last issue of Genesis, 44/2017, «Après le texte»(http://genesis.revues.org/1579).